2021
DOI: 10.1002/advs.202104036
|View full text |Cite
|
Sign up to set email alerts
|

Smart Flow Electrosynthesis and Application of Organodisulfides in Redox Flow Batteries

Abstract: Electrochemical techniques have been recognized as an environmentally friendly and sustainable synthetic way to form organodisulfides. However, searching for optimum conditions which suffers from time/material-consuming caused by the uncertainty of reactant consumption has hindered its rapid and large-scale development. Inspired by advanced nonaqueous redox flow batteries (NARFBs) technology, it is proposed a smart flow electrosynthesis (SFE) method of organodisulfides that the voltage curve of NARFBs can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…(e) Long-cycling stability of EXDS and IXDS over 1000 cycles at 0.5 mA cm –2 . Reproduced with permission from ref . Copyright 2021, Wiley-VCH.…”
Section: Organosulfur In Lithium Redox Flow Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Long-cycling stability of EXDS and IXDS over 1000 cycles at 0.5 mA cm –2 . Reproduced with permission from ref . Copyright 2021, Wiley-VCH.…”
Section: Organosulfur In Lithium Redox Flow Batteriesmentioning
confidence: 99%
“…Chen et al found that the ether electrolyte containing ethylxanthic disulfide (EXDS) produces a lot of precipitation after a period of standing, indicating that the EXDS is unstable in the electrolyte. 327 On the contrary, isopropylxanthic disulfide (IXDS) can be stabilized in the ether electrolyte, and no precipitation is observed for a long time. The cycling life test shows that a high capacity retention of 76% over 1000 cycles is achieved for the IXDS-based catholyte, which is higher than 19% of EXDS (Figure 42e), suggesting that the molecules being stable in the electrolyte are more suitable as active materials for Li-RFBs.…”
Section: Elongation Of Cycling Stabilitymentioning
confidence: 99%
“…Nowadays, energy storage technologies, including pumped‐hydro, 1 compressed air, 2 and electrochemical energy storage, 3–5 are more and more necessary to improve the utilization efficiency of renewable energy 6 . Among them, flow batteries have been considered to be one of the most suitable technologies for large‐scale energy storage 7–12 . Particularly, the emerging aqueous zinc‐based flow batteries 13–17 (ZFBs) have attracted extensive interest of researchers in recent, owing to the high energy density, long cycle life, safety and environmental friendliness 18 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Among them, flow batteries have been considered to be one of the most suitable technologies for large-scale energy storage. [7][8][9][10][11][12] Particularly, the emerging aqueous zinc-based flow batteries [13][14][15][16][17] (ZFBs) have attracted extensive interest of researchers in recent, owing to the high energy density, long cycle life, safety and environmental friendliness. 18 However, the uneven zinc plating/stripping process during the charge/discharge cycles causes serious dendrite problem, which is known as one of the most critical challenges for ZFBs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 10 y, most of the work on RFBs has focused on material screening and optimization ( 17 , 18 ). RSSR molecules are highly soluble in organic solvents, which makes them suitable as active materials in catholytes for RFBs ( 19 22 ). To improve the achievable capacity and reaction kinetics of RSSR, Weng et al.…”
mentioning
confidence: 99%